KEPENTINGAN SINGAPURA BERINVESTASI DI SEKTOR PARIWISATA PULAU BINTAN - Herman, Rafif Basya’ir; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze Singapore’s interests in investing in the tourism sector of Bintan Island and to identify the actors, policies, and programs involved in the process. Bintan Island, which is geographically close and historically linked to Singapore, holds a strategic position in promoting regional cooperation in investment and tourism. This research employs a qualitative approach with a descriptive-analytical method. The theoretical framework includes the Theory of National Interest, State Investment Theory, Foreign Direct Investment (FDI) Theory, and Economic Liberalism Theory. These theories are used to explain how Singapore’s national policies and economic strategies drive its outward investment expansion, particularly to Bintan Island, as well as how Indonesia’s policies—through the Special Economic Zone (SEZ)—support such investment collaboration. The findings reveal that Singapore’s investment interests in Bintan Island are not solely economic, such as market expansion and tourism development, but also encompass political, geopolitical, and economic diplomacy aspects. This investment strengthens Singapore’s position as a regional economic hub while reinforcing bilateral relations with Indonesia. Moreover, the involvement of various actors—including government bodies, private sectors, and financial institutions—demonstrates that the investment is a synergy of shared policies and mutual interests. Nevertheless, challenges such as local economic disparity, potential foreign dominance, and environmental sustainability issues remain crucial considerations in maintaining the balance of benefits from this cross-border investment. Keywords: Foreign investment, tourism, bilateral relations, national interests.